Fine-Mapping and Functional Analyses of a Candidate Gene Controlling Isoflavone Content in Soybeans Seed - Li, Ruiqiong; Zou, Jianan; Sun, Dongming; Jing, Yan; Wu, Depeng; Lian, Ming; Teng, Weili; Zhan, Yuhang; Li, Wenbin; Zhao, Xue; Han, Yingpeng (Frontiers in Plant Science, 2022)
Isoflavones, one of the most important secondary metabolites produced by soybeans (Glycine max (L.) Merr.), are important for a variety of biological processes, and are beneficial for human health. To identify genetic loci underlying soybean isoflavone content, a mapping population containing 119 F5:18 recombinant inbred lines, derived by crossing soybean cultivar ‘Zhongdou27’ with ‘Dongong8004’, was used. We identified 15 QTLs associated with isoflavone contents. A novel loci, qISO19-1, was mapped onto soybean chromosome 19 and was fine-mapped to a 62.8 kb region using a BC2F2 population. We considered GmMT1 as a candidate gene for the qISO19-1 locus due to the significant positive correlation recovered between its expression level and isoflavone content in the seeds of 43 soybean germplasms. Overexpression of GmMT1 in Arabidopsis and soybean cultivars increased isoflavone contents. Transgenic soybeans overexpressing GmMT1 also exhibited improved resistance to pathogenic infection, while transgenic Arabidopsis resisted salt and drought stress.